(NmEHANI^ESKOE PIANINO(B: [(NrOMAN(B]; s (NrASSKAZY (B/ s (N~ASTX(B1s - (NwONNEGUT(B, (NkURTs ((NmOSKWA(B: s (NsTART(B, s, 1992)
(NwNECIKLOWYJ ROMAN I IZBRANNYE RASSKAZY IZ SBORNIKA (B"(NdOBRO POVALOWATX W OBEZXQNNIK(B".s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NnAU^NAQ FANTASTIKAs -- (NrASSKAZYs